Critical success factors for Lean Six Sigma in business school: A view from the lecturers - Tan Owee Kowang; Lim Peidi; Lim Kim Yew; Ong Choon Hee; Goh Chin Fei; Baharudin Kadir (Institute of Advanced Engineering and Science, 2022)
Lean is a process improvement approach to improve organization’s efficiency by identifying and eliminate non-value-added activities, while Six Sigma is a methodology focused on reduction of process variation. The integration of both, namely Lean Six Sigma (LSS) drives organization on waste elimination, variation reduction and value creation, which ultimately enhancing organizational performance. LSS has been viewed by prior scholars as one of effective approach for business improvement regardless of manufacturing or services industry. However, the research of LSS in education sector, particularly for business school is relatively lacking. Hence, this research aimed to identify the critical success factors (CSFs) for LSS within a business school in Malaysia. The research also aimed to explore the relationship between the LSS, CSFs, and organization performance. There were six CSFs identified from literature review, while organization performance is assessed via the concept of system theory. The research was quantitative based with the lecturers in the business school as the targeted population. Questionnaire was distributed based on stratified sampling plan with 69 responded. Descriptive and Pearson correlation analysis result revealed that lecturers within the business school perceived that all the six LSS CSFs as “very important”, and strongly correlated with organization performance, except CSF “project selection and prioritization”. As implication, finding from this research suggested that the adaption of LSS between manufacturing and education sectors shared the commonality in term of CSF. However, the business school should look into project proposal from the lecturers’ perspective as an alternate source of process improvement opportunity.